Effects of N application methods on cotton yield and fertilizer N recovery efficiency in salinity fields with drip irrigation under mulch film using 15N tracing technique - Luo, Zhen; Tang, Wei; Wang, Xiaowen; Lu, Hequan; Li, Chenyang; Liang, Jun; Kong, Xiangqiang (Frontiers in Plant Science, 2024)
Drip irrigation under mulch film promotes a non-uniform salinity distribution in salt fields. To study the effect of different nitrogen (N) application methods on cotton plant growth, yield and fertilizer N recovery efficiency (FNRE) using drip irrigation under mulch film conditions, three N application methods were assigned: N applied under mulch film (low-salinity area; UM), N applied between mulch films (high-salinity area; BM), and half N applied under mulch film and half between mulch films (HUHB). Plant height, photosynthesis, Chl content, boll load, biomass, boll weight and boll density under UM were all significantly higher than those under the other two treatments. The N absorption of UM was higher than in the other two treatments, which might be attributed to the expression of GHNRT1.5 and GHNRT2.1. The net NO3-influx in the roots in UM increased significantly compared with that in BM. The yield and FNRE of UM were 3.9% and 9.1%, respectively, and were 26.52% and 90.36% higher than under HUHB and BM treatments.Accordingly，UM not only improved cotton yield but also alleviated the pollution of N residue on drip irrigation under mulch film conditions in salt areas.